Incidence of SARS-CoV-2 in people with cystic fibrosis in Europe between February and June 2020 - GÖKDEMİR, YASEMİN (ELSEVIER, 2021)
Background: Viral infections can cause significant morbidity in cystic fibrosis (CF). The current Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic could therefore have a serious impact on the health of people with CF (pwCF). Methods: We used the 38-country European Cystic Fibrosis Society Patient Registry (ECFSPR) to collect case data about pwCF and SARS-CoV-2 infection. Results: Up to 30 June 2020, 16 countries reported 130 SARS-CoV-2 cases in people with CF, yielding an incidence of 2.70/10 0 0 pwCF. Incidence was higher in lung-transplanted patients (n = 23) versus non transplanted patients (n = 107) (8.43 versus 2.36 cases/10 0 0). Incidence was higher in pwCF versus the age-matched general population in the age groups < 15, 15-24, and 25-49 years (p < 0.001), with similar trends for pwCF with and without lung transplant. Compared to the general population, pwCF (regardless of transplantation status) had significantly higher rates of admission to hospital for all age groups with available data, and higher rates of intensive care, although not statistically significant. Most pwCF recovered (96.2%), however 5 died, of whom 3 were lung transplant recipients. The case fatality rate for pwCF (3.85%, 95% CI: 1.26-8.75) was non-significantly lower than that of the general population (7.46%; p = 0.133). Conclusions: SARS-CoV-2 infection can result in severe illness and death for pwCF, even for younger patients and especially for lung transplant recipients. PwCF should continue to shield from infection and should be prioritized for vaccination. (c) 2021 The Authors. Published by Elsevier B.V. on behalf of European Cystic Fibrosis Society. This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ )
Keywords: Cystic fibrosis; Covid-19; SARS-CoV-2; Europe; Incidence; Epidemiology; IMPACT